2019
DOI: 10.1038/s41598-019-39651-y
|View full text |Cite
|
Sign up to set email alerts
|

MRI-based Radiomics nomogram to detect primary rectal cancer with synchronous liver metastases

Abstract: Synchronous liver metastasis (SLM) remains a major challenge for rectal cancer. Early detection of SLM is a key factor to improve the survival rate of rectal cancer. In this radiomics study, we predicted the SLM based on the radiomics of primary rectal cancer. A total of 328 radiomics features were extracted from the T2WI images of 194 patients. The least absolute shrinkage and selection operator (LASSO) regression was used to reduce the feature dimension and to construct the radiomics signature. after LASSO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 39 publications
0
50
0
Order By: Relevance
“…These features can characterize the heterogeneity of cancer and reflect changes in the tumor microstructure (17). The most robust features were used for manual correction purposes to improve the usefulness of the model (18). The Spearman's rank test was used to assess the correlation coefficients between features of set-A (Radiologist A) and set-B (Radiologist B).…”
Section: Extraction Of Radiomic Featuresmentioning
confidence: 99%
“…These features can characterize the heterogeneity of cancer and reflect changes in the tumor microstructure (17). The most robust features were used for manual correction purposes to improve the usefulness of the model (18). The Spearman's rank test was used to assess the correlation coefficients between features of set-A (Radiologist A) and set-B (Radiologist B).…”
Section: Extraction Of Radiomic Featuresmentioning
confidence: 99%
“…Radiomics can be combined with the imaging appearance to further improve the differential diagnosis ability of the lesion (30,31). The AK, an imaging analytic software used in this study, has been used in many research reports (32,33). A previous study showed that radiomic feature-based CT imaging signatures allow the prediction of lymph node metastasis in cancer and could facilitate the preoperative individualized prediction of lymph node status (20).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, 52 cases were diagnosed with mMCAi. All patients were divided randomly into training ( n = 87) and validation ( n = 39) sets according to a 7:3 ratio ( Shu et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…The inter-rater reliability on ROI segmentation of MCA territory was computed by comparing the measurement from rater B (15 years of experience in interpreting neurological CT scans) and the measurement from rater A (10 years of experience in interpreting neurological CT scans) in 30 randomly selected patients by κ test. Images underwent preprocessing with AK software (Artificial Intelligence Kit V3.0.0.R, GE Healthcare), which included image interpolation, intensity normalization, and gray-level discretization as described previously ( Shu et al, 2019 ). Next, we calculated the texture features including histogram, formfactor, haralick, run-length matrix (RLM), gray-level co-occurrence matrix (GLCM), and gray-level size zone matrix (GLSZM) with AK software (Artificial Intelligence Kit V3.0.0.R, GE Healthcare).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation